Long-term NMDAR antagonism correlates reduced astrocytic glutamate uptake with anxiety-like phenotype - Zimmer, Eduardo R.; Torrez, Vitor R.; Kalinine, Eduardo; Augustin, Marina C.; Zenki, Kamila C.; Almeida, Roberto F.; Hansel, Gisele; Muller, Alexandre P.; Souza, Diogo O.; Machado-Vieira, Rodrigo; Portela, Luis V. (Frontiers in Cellular Neuroscience, 2015)
The role of glutamate N-methyl-D-Aspartate receptor (NMDAR) hypofunction has been extensively studied in schizophrenia; however, less is known about its role in anxiety disorders. Recently, it was demonstrated that astrocytic GLT-1 blockade leads to an anxiety-like phenotype. Although astrocytes are capable of modulating NMDAR activity through glutamate uptake transporters, the relationship between astrocytic glutamate uptake and the development of an anxiety phenotype remains poorly explored. Here, we aimed to investigative whether long-term antagonism of NMDAR impacts anxiety-related behaviors and astrocytic glutamate uptake. Memantine, an NMDAR antagonist, was administered daily for 24 days to healthy adult CF-1 mice by oral gavage at doses of 5, 10 or 20 mg/kg. The mice were submitted to a sequential battery of behavioral tests (open field, light-dark box and elevated plus-maze tests). We then evaluated glutamate uptake activity and the immunocontents of glutamate transporters in the frontoparietal cortex and hippocampus. Our results demonstrated that long-term administration of memantine induces anxiety-like behavior in mice in the light-dark box and elevated plus-maze paradigms. Additionally, the administration of memantine decreased glutamate uptake activity in both the frontoparietal cortex and hippocampus without altering the immunocontent of either GLT-1 or GLAST. Remarkably, the memantine-induced reduction in glutamate uptake was correlated with enhancement of an anxiety-like phenotype. In conclusion, long-term NMDAR antagonism with memantine induces anxiety-like behavior that is associated with reduced glutamate uptake activity but that is not dependent on GLT-1 or GLAST protein expression. Our study suggests that NMDAR and glutamate uptake hypofunction may contribute to the development of conditions that fall within the category of anxiety disorders.